Single-stage MBBR using novel carriers to remove nitrogen in rural domestic sewage: The effect of carrier structure on biofilm morphology and SND. Issue 5 (October 2022) - Wu, Yunpeng; Wan, Ajun; Zhao, Bi; Xue, Song; Xu, Ao
Abstract: A narrowing channel rotiform carrier was designed and applied to treat rural domestic sewage. The performance of the carrier on carbon and nitrogen removal during start-up and under difference dissolved oxygen (DO) concentrations were studied through numerical simulation and experiment. The microbial community structure and evolution on biofilms were studied by high-throughput sequencing. And the impact of carrier structure on biofilm morphology and simultaneous nitrification and denitrification was analyzed. The channel of the carrier facilitated the irreversible attachment of the microbe, which provided the reactor with a start-up period within ten days. Under the DO concentration of 1.7–2.3 mg/L, the chemical oxygen demand (COD) and total nitrogen (TN) removal rates of the carrier were higher than 88.4% and 67.8%, respectively. Both the experimental and sequencing results proved that simultaneous nitrification and denitrification occurred in the reactor, with Flavobacterium and Hydrogenophaga as the key genera for denitrification. A filamentous biofilm which is rarely reported grew on the outer edge of the carrier, and its consumption of dissolved oxygen may be the main reason for the growth of denitrifying bacteria in the channel. Graphical Abstract: ga1 Highlights: A novel carrier is designed to remove nitrogen in single-stage moving bed biofilm reactor. The reactor starts up in ten days. Carbon and nitrogen are efficiently removed under the dissolved oxygen value of 2 mg/L. Flavobacterium and Hydrogenophaga are the key genera for denitrification. Different morphologies of biofilms are present on the carrier.